2016
DOI: 10.3889/oamjms.2016.040
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of the Oxidative Stress in Blood of Patients in Dependence of Community-Acquired Pneumonia Severity

Abstract: BACKGROUND:At the present time the alternation of the oxidative metabolism is considered as one of the leading pathogenic mechanisms in the development and progression of community-acquired pneumonia (CAP). However the nature and direction of the oxidative protein changes in CAP patient’s blood had been almost unexplored.AIM:To define oxidative and modified proteins in erythrocytes and blood plasma of CAP patients.MATERIAL AND METHODS:Blood plasma and erythrocytes obtained from: 42 patients with moderate sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…They found that decreased serum TOS is associated with CAP. Muravlyova et al18 found that malondialdehyde and reactive carbonyl derivatives were significantly lower in CAP patients than in controls. Castillo et al14 showed that the antioxidant capacity of plasma, as well as glutathione and glutathione disulfide levels, were lower than in controls.…”
Section: Discussionmentioning
confidence: 97%
“…They found that decreased serum TOS is associated with CAP. Muravlyova et al18 found that malondialdehyde and reactive carbonyl derivatives were significantly lower in CAP patients than in controls. Castillo et al14 showed that the antioxidant capacity of plasma, as well as glutathione and glutathione disulfide levels, were lower than in controls.…”
Section: Discussionmentioning
confidence: 97%
“…[11][12][13][14][15] Several recent studies have evaluated the associations between CAP and the oxidant and antioxidant statuses. 9,10,16,17 Reactive oxygen species (ROS) occur normally in physiological conditions, and they are counterbalanced by oxidantantioxidant mechanisms. In CAP, these mechanisms are destroyed by phagocytes acting via the primary defense mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, neutrophils play a dual role: on the one hand, they perform a protective function; on the other, they are potential mediators of tissue damage. A sufficient number of studies have been devoted to the study of indices of oxidative stress in the blood to assess the severity of the pathological process, but the number of studies of indices of oxidative stress of neutrophils in CAP patients with chronic obstructive pulmonary disease (COPD) and patients with CAP depending on the degree of disease severity is limited [ 6 , 7 ]. In this aspect, the study of neutrophils and their functional and metabolic status is one of the most urgent and promising tasks, since their condition largely determines the development and outcomes of the disease.…”
Section: Introductionmentioning
confidence: 99%